Thin films CdS/CdTe solar cells with different activation processes base layer - Khrypunov, G.S.; Shelest, T.N.; Li, T.N.; Meriuts, A.V.; Kovtun, N.A.; Makarov, A.V.; Avksentyeva, L.V. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2011)
Shown in this work is the possibility to create industrial technology for production of solar cells FTO/CdS/CdTe. The technology includes annealing in freon processing step for activation of cadmium telluride base layers deposited by thermal vacuum evaporation. Solar cells with efficiency of 7% have been obtained. Structural and morphological researches allowed to identify interrelation between photovoltaic characteristics and features of the recrystalization process in base layers after annealing in freon as compared with the standard chloride treatment.